2017
DOI: 10.1039/c7cp05530g
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cation mixing controlled by thermal treatment duration on the electrochemical stability of lithium transition-metal oxides

Abstract: Lithium cathode materials have been considered as promising candidates for energy storage applications because of their high power/energy densities, low cost, and low toxicity. However, the Li/Ni cation mixing limits their application as practical electrode materials. The cation mixing of lithium transition-metal oxides, which was first considered only as the origin of performance degeneration, has recently been reconsidered as a way to stabilize the structure of active materials. Here we find that as the dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
67
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 44 publications
1
67
0
Order By: Relevance
“…Consequently, the amount of Ni 2+ increases and results in more Li/Ni anti-sites at the particle surface, stabilizing Li layers during Li insertion/extraction. [11] The strategy of constructing Mn-rich surface, including core-shell and concentration-gradient structure, [9] can also effectively protect the particle surface of high-Ni layered oxides, and deliver excellent electrochemical performance. Nevertheless, such doping strategy could not completely prevent the formation of the detrimental surficial residues, including rock-salt phase and Li 2 CO 3 at the particle surface.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the amount of Ni 2+ increases and results in more Li/Ni anti-sites at the particle surface, stabilizing Li layers during Li insertion/extraction. [11] The strategy of constructing Mn-rich surface, including core-shell and concentration-gradient structure, [9] can also effectively protect the particle surface of high-Ni layered oxides, and deliver excellent electrochemical performance. Nevertheless, such doping strategy could not completely prevent the formation of the detrimental surficial residues, including rock-salt phase and Li 2 CO 3 at the particle surface.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies think Ni at Li sites block the Li diffusion path. [18][19][20][21] The optimal degree of Ni 2+ occupancy in the Li + sites can improve the electrochemical performance of layered Li(Ni x Co y Mn z )O 2 (NMC) materials and offer an electrostatic repulsion force to prevent more transition metal migration. [12][13][14][15] In order to reduce antisite concentration, many approaches are utilized to improve the electrochemical performance, such as adjusting synthetic process, surface coating, and element doping.…”
mentioning
confidence: 99%
“…Moreover, the Ni 2+ takes active Li + place, which result in first-cycle reversible capacity loss and poor layered structure stability. [19] Cho et al found that the coating Ni-based material with a thin antisite layer demonstrated an excellent cycling property under elevated temperature test, which is mainly ascribed to the unique pillar layer including moderate antisite concentration. Zhou and co-workers reduced the antisite of LiNi 0.8 Co 0.15 Al 0.05 O 2 materials via control of oxygen flow rate during sintering.…”
mentioning
confidence: 99%
See 2 more Smart Citations